The Vermes quest: the significance of Geza Vermes for Jesus research - Møller, Hilde Brekke (Library of New Testament studies, 2017)
"Geza Vermes is a household name within the study of the historical Jesus, and his work is associated with a significant change within mainstream Jesus research, typically labelled 'the third quest'. Since the publication of Jesus the Jew in 1973, many notable Jesus scholars have interacted with Vermes's ideas and suggestions, yet their assessments have so far remained brief and ambiguous. Hilde Brekke Moller explores the true impact of Vermes's Jesus research on the perceived change within Jesus research in the 1980s, and also within third quest Jesus research, by examining Vermes's work and the reception of his work by numerous Jesus scholars. Moller looks in particular depth at the Jewishness of Jesus, the Son-of-Man problem, and Vermes's suggestion that Jesus was a Hasid, all being aspects of Vermes's work which have attracted the most scholarly attention. Moller's research-historical approach focuses not only on the leading scholars of the field such as E.P. Sanders, J.D. Crossan, J.P. Meier and C.A. Evans, but also sheds light on underplayed aspects of previous research, and responds to the state of affairs for recent research by challenging the rhetoric of current historical Jesus scholarship." -- from the publisher